Zinc uptake and radial transport in roots of arabidopsis thaliana: a modelling approach to understand accumulation - Claus, Juliane; Bohmann, Ansgar; Chavarría-Krauser, Andrés (Annals of botany, 2013)
Zinc uptake in roots is believed to be mediated by ZIP (ZRT-, IRT-like Proteins) transporters. Once inside the symplast, zinc is transported to the pericycle, where it exits by means of HMA (Heavy Metal ATPase) transporters. The combination of symplastic transport and spatial separation of influx and efflux produces a pattern in which zinc accumulates in the pericycle. Here, mathematical modelling was employed to study the importance of ZIP regulation, HMA abundance and symplastic transport in creation of the radial pattern of zinc in primary roots of Arabidopsis thaliana. A comprehensive one-dimensional dynamic model of radial zinc transport in roots was developed and used to conduct simulations. The model accounts for the structure of the root consisting of symplast and apoplast and includes effects of water flow, diffusion, and cross-membrane transport via transporters. It also incorporates the radial geometry and varying porosity of root tissues, as well as regulation of ZIP transporters. Steady state patterns were calculated for various zinc concentrations in the medium, water influx and HMA abundance. The experimentally observed zinc gradient was reproduced very well. Increase of HMA or decrease in water influx led to loss of the gradient. The dynamic behaviour for a change in medium concentration and water influx was also simulated showing short adaptation times in the range of seconds to minutes. Slowing down regulation led to oscillations in expression levels, suggesting the need for rapid regulation and existence of buffering agents. The model captures the experimental findings very well and confirms the hypothesis that low abundance of HMA4 produces a radial gradient in zinc concentration. Surprisingly, transpiration was found to be also a key parameter. The model suggests that ZIP regulation takes place on a comparable time scale as symplastic transport.
Published electronically: 19 December 2012
Gesehen am 23.04.2021